Understanding of Students Regarding Paylater Services and Its Impact on Usage Decisions - Dewi, Khalisa Novita; Nurindah, Marisa Nabila; Hamzah, Nurah Alisha; Kholmi, Masiyah (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2025)
Digital financial services like Paylater are increasingly used by students, but there are not many studies examining how individual understanding of these services affects their usage decisions. Most previous research has focused more on external factors such as social influence and consumer behavior, but has not deeply examined the relationship between students' understanding and the decisions they make. This study aims to examine how students at Universitas Muhammadiyah Malang understand the Paylater service and how that understanding impacts their usage decisions. This study uses a descriptive qualitative approach with data collection techniques in the form of semi-structured interviews with ten purposively selected students. The analysis process was conducted using thematic analysis methods, through stages of transcription, re-reading, coding, grouping codes into sub-themes and themes, and drawing conclusions. The research results show that students understand Paylater as an interest-bearing digital loan service and associate it with religious values, particularly in relation to usury. This understanding directly influences their decisions, where the majority choose not to use the service. This study recommends that future research delve deeper into the dynamics of user understanding of digital services in a broader context.